PUSAT LAYANAN ANAK USIA DINI TERPADU SEBAGAI TEMPAT PENYELENGGARAAN PENDIDIKAN INKLUSI DENGAN PENDEKATAN PSIKOLOGI ARSITEKTUR DI SURAKARTA - Devi Rusdiana Putri; Hadi Setyawan; Bambang Triratma (ARSITEKTURA, 2016)
Planning and designing Children Care and Education Centre in Surakarta, that running out inclusive education, is motivated by the importance of developing the potential of children at early age. But unfortunately, this is not supported by the availability of educational facilities in the early levels, especially those who are able to serve both children with and without disabilities. Inclusive learning method is chosen as the most suitable learning method for both children with and without disabilities. The main issue of this design is how building’s elements accommodate both children with and without disabilities and support inclusive environment. The implementation of psychology of architecture’s concepts is used to support the growth and development of both children with and without disabilities through internal and external stimulation. Those stimulations are given through activity and architectural element such as room’s layout, room’s interior, building façade and complementary elements like landscape. Those would support the interaction between both children with and without disabilities in creating inclusive environment that support the learning process and development of every child.